Analysis of the Effect of Spiral Confinement in the Compression Zone on Reinforced Concrete Beam’s Ductility and Flexural Strength Using Moment-Curvature Relationship - Marley Kristianto; Indradi Wijatmiko; Ari Wibowo; Christin Remayanti (Jurnal Mahasiswa Jurusan Teknik Sipil, 2024)
Structural elements such as beams requires high ductility to avoid brittle failure during seismic events. One approach for increasing beam ductility involves adding additional confinement in the compression zone. This study investigates the effect of additional spiral confinement in the compression zone to the beam’s ductility and flexural strength. Numerical analysis is conducted for beams with and without additional confinement. The flexural strength is represented with moment of resistance and the ductility is expressed in terms of curvature ductility. Trilinear moment-curvature curve is used as the instrument to observe the effect of the additional spiral confinement. Experimental test was also conducted for both specimen which then be compared to the theoretical result. The results conclude that by adding additional spiral confinement the ductility of reinforced concrete [RC] beam is improved drastically while the flexural strength is improved by a small margin. Keywords: spiral confinement, curvature ductility, flexural strength, moment-curvature curve.